The Effect of Intra-articular Corticosteroids on Articular Cartilage: A Systematic Review. Issue 5 (27th April 2015) - Wernecke, Chloe; Braun, Hillary J.; Dragoo, Jason L.
Background: Intra-articular (IA) corticosteroid therapy has been used for the treatment of inflammation and pain in the knee since the 1950s. Purpose: To review the current literature on the effects of IA corticosteroids on articular cartilage. Study Design: Systematic review. Methods: A MEDLINE and SCOPUS database search was performed, and studies were selected for basic science and clinical trial research on corticosteroids with direct outcome measures of cartilage health. Preliminary searches yielded 1929 articles, and final analysis includes 40 studies. Results: Methylprednisolone, dexamethasone, hydrocortisone, betamethasone, prednisolone, and triamcinolone were reported to display dose-dependent deleterious effects on cartilage morphology, histology, and viability in both in vitro and in vivo models. The beneficial animal in vivo effects of methylprednisolone, hydrocortisone, and triamcinolone occurred at low doses (usually <2-3 mg/dose or 8-12 mg/cumulative total dose in vivo), at which increased cell growth and recovery from damage was observed; the single human clinical trial indicated a beneficial effect of triamcinolone. However, at higher doses (>3 mg/dose or 18-24 mg/cumulative total dose in vivo), corticosteroids were associated with significant gross cartilage damage and chondrocyte toxicity. Dose and time dependency of corticosteroid chondrotoxicity was supported in the in vitro results, however, without clear dose thresholds. Conclusion: Corticosteroids have a time- and dose-dependent effect on articular cartilage, with beneficial effects occurring at low doses and durations and detrimental effects at high doses and durations. Clinically, beneficial effects are supported for IA administration, but the lowest efficacious dose should be used.